Dual-Credit Courses and the Road to College: Experimental Evidence from Tennessee - Steven W. Hemelt; Nathaniel L. Schwartz; Susan Dynarski (Institute of Labor Economics (IZA), 2019)
Dual-credit courses expose high school students to college-level content and provide the opportunity to earn college credits, in part to smooth the transition to college. With the Tennessee Department of Education, we conduct the first randomized controlled trial of the effects of dual-credit math coursework on a range of high school and college outcomes. We find that the dual-credit advanced algebra course alters students' subsequent high school math course-taking, reducing enrollment in remedial math and boosting enrollment in precalculus and Advanced Placement math courses. We fail to detect an effect of the dual-credit math course on overall rates of college enrollment. However, the course induces some students to choose four-year universities instead of two-year colleges, particularly for those in the middle of the math achievement distribution and those first exposed to the opportunity to take the course in 11th rather than 12th grade. We see limited evidence of improvements in early math performance during college.
Keywords: I21; I23; I24; I28; 330; dual-credit courses; college enrollment; college choices; math coursework